The role of cell membrane-coated nanoparticles as a novel treatment approach in glioblastoma - Allami, Pantea; Heidari, Arash; Rezaei, Nima (Frontiers in Molecular Biosciences, 2023)
Glioblastoma multiform (GBM) is a grade IV glioma and the most prevalent primary brain malignancy in adults, causing numerous mortalities annually. The median survival of patients with GBM after diagnosis does not exceed 18 months. Various tumor characteristics, including GBM stem cell (GSC) features, intratumoral heterogeneity, and the blood-brain barrier (BBB) properties, make GBM an incurable disease. The conventional treatment of this tumor, including maximal surgery, chemotherapy, and radiotherapy, could not lead to much increase in the life expectancy. Therefore, several innovative approaches for treating GBM have been suggested in recent years of struggling with this disease. As an emerging science phenomenon, nanotechnology introduced a new generation of drugs in oncology. However, although nano-drugs can pass the BBB, they still have significant side effects and short circulation time in the body. In this regard, coating drug-loaded nanoparticles (NP) with biomimicking agents could prolong and specify the effectiveness of these agents. Hence, the cell membrane (CM)-coated NPs emerged as a novel treatment approach in GBM patients. In this regard, CM-coated NPs could be beneficial in causing efficient drug delivery to the tumor site and could enhance the effectiveness of conventional treatment. The present review provides an overview of the characteristics of CM-coated NPs and comprehensively investigates their application as a novel treatment approach in GBM.